(untitled) (Architecture Image Studies, 2025)
Brand equity plays a crucial role in shaping the success of tourism destinations, influencing visitor perception, loyalty, and overall competitiveness. This study examines the factors affecting brand equity in the context of tourism destinations, focusing on four key independent variables: visitors’’s Perception, Food Quality, Cognitive Image, and Brand Loyalty. The research employs a quantitative approach, utilizing a Likert-scale questionnaire to collect data from respondents. Pearson correlation and multiple regression analysis assessed the relationship between these factors and brand equity. The findings indicate that all four independent variables significantly influence brand equity, with Food Quality and Brand Loyalty demonstrating the most substantial impact. The multiple regression results further validate these relationships, confirming that Visitor’s Perception, Food Quality, and Cognitive Image positively contribute to brand equity, whereas Brand Loyalty shows a negative but significant influence. These insights provide valuable implications for tourism marketers and destination managers, emphasizing the need to enhance service quality, strengthen customer loyalty strategies, and create a positive cognitive image to build a sustainable competitive advantage. This study contributes to the existing body of knowledge on destination brand equity and offers strategic recommendations for improving the brand positioning of tourism destinations. Future research could explore additional moderating variables and examine cross-cultural perspectives to provide a more comprehensive understanding of consumer behaviour in tourism branding.